2016
DOI: 10.1007/s11948-016-9820-z
|View full text |Cite
|
Sign up to set email alerts
|

Plagiarism, Cheating and Research Integrity: Case Studies from a Masters Program in Peru

Abstract: Plagiarism is a serious, yet widespread type of research misconduct, and is often neglected in developing countries. Despite its far-reaching implications, plagiarism is poorly acknowledged and discussed in the academic setting, and insufficient evidence exists in Latin America and developing countries to inform the development of preventive strategies. In this context, we present a longitudinal case study of seven instances of plagiarism and cheating arising in four consecutive classes (2011–2014) of an Epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
0
19
0
4
Order By: Relevance
“…Consistent with this finding, plagiarism is reported quite frequently in the early stages of a researcher's career 14 whereas relatively fewer studies report such incidences in students of higher grades with more research experience. 15 Furthermore, the study by Shirazi et al (2010) 7 discussed herein also revealed a better understanding of self-plagiarism among faculty members in contrast to medical students due to differences in prior research experiences.…”
Section: Discussionmentioning
confidence: 57%
“…Consistent with this finding, plagiarism is reported quite frequently in the early stages of a researcher's career 14 whereas relatively fewer studies report such incidences in students of higher grades with more research experience. 15 Furthermore, the study by Shirazi et al (2010) 7 discussed herein also revealed a better understanding of self-plagiarism among faculty members in contrast to medical students due to differences in prior research experiences.…”
Section: Discussionmentioning
confidence: 57%
“…Four cases of plagiarism ( N = 2) and cheating ( N = 2) in a master’s program at UPCH led to the realization of the extent of research and academic misconduct events observed and the need for research integrity awareness and training. 9 Greater attention was given to potential research misconduct events, and responsible conduct of research (RCR) training was enhanced, with curricula that included lectures on the role of mentoring as a mechanism to prevent misconduct. In addition, a mentoring program was established in 2012 at the U.S.…”
Section: Case 1—upch Perumentioning
confidence: 99%
“…Content was developed in part to address the previously described plagiarism and cheating cases observed in a local academic program and includes brief examinations and a completion diploma. 9 In 2015, the Peruvian National Science and Technology Council (CONCYTEC for its acronym in Spanish) launched a new policy requiring CRI completion to apply for grant opportunities and be registered as investigators. 11,12 In 2017, UPCH added the CRI completion requirement for students, faculty, and investigators applying to grants or requesting institutional review board (IRB) review.…”
Section: Case 1—upch Perumentioning
confidence: 99%
“…However, there is limited research on the topic within Latin America. Plagiarism is characterized as a widespread misconduct, but it “is poorly acknowledged and discussed in the academic setting, and insufficient evidence exists in Latin America and developing countries to inform the development of preventive strategies” (Carnero et al, 2017: 1183).…”
Section: Introductionmentioning
confidence: 99%